2006
DOI: 10.1002/jmr.761
|View full text |Cite
|
Sign up to set email alerts
|

Metal ions-dependent peroxidase and oxidoreductase activities of polyclonal IgGs from the sera of Wistar rats

Abstract: We present evidence showing that a small fraction of electrophoretically homogeneous IgGs from the sera of healthy Wistar rats is bound with several different Me2+ ions and oxidizes 3,3'-diaminobenzidine through a peroxidase activity in the presence of H2O2 and through an oxidoreductase activity in the absence of H2O2. During purification on Protein A-Sepharose and gel filtration, the polyclonal IgGs partially lose the Me2+ ions. Therefore, in the absence of external metal ions, the specific peroxidase activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
111
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 29 publications
(114 citation statements)
references
References 43 publications
3
111
0
Order By: Relevance
“…10/30 column in the acidic buffer destroying non-covalent protein complexes as in (Ikhmyangan et al, 2005(Ikhmyangan et al, , 2006a. After each chromatography the IgG fraction was collected to cooled tubes containing 50 ml of 0.5 M K-phosphate (pH 8.5) and then additionally neutralized with this buffer and dialysed against 20 mM K-phosphate (pH 7.0).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…10/30 column in the acidic buffer destroying non-covalent protein complexes as in (Ikhmyangan et al, 2005(Ikhmyangan et al, , 2006a. After each chromatography the IgG fraction was collected to cooled tubes containing 50 ml of 0.5 M K-phosphate (pH 8.5) and then additionally neutralized with this buffer and dialysed against 20 mM K-phosphate (pH 7.0).…”
Section: Methodsmentioning
confidence: 99%
“…During purification on Protein A-Sepharose and gel filtration, the pIgGs partially lose the Me 2þ ions. Therefore, the specific peroxidase and oxidoreductase activities of IgGs depending on a preparation, increase $8-120-fold after addition of external Cu 2þ or Fe 2þ (Ikhmyangan et al, 2006a). Chromatography of the IgGs on Chelex-100 leads to the adsorption of a small IgG fraction containing metal ions and to its separation into many different subfractions demonstrating various affinities to the chelating sorbent and increased levels of the specific oxidoreductase and peroxidase activities (Ikhmyangan et al, 2006a).…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…Rabbit IgGs against DNase I, DNase II, RNase A, DNA, and RNA (Krasnorutskii et al, 2008a(Krasnorutskii et al, , 2008b(Krasnorutskii et al, , 2008c(Krasnorutskii et al, , 2008d(Krasnorutskii et al, , 2009, similarly to human AI Abzs (Nevinsky et al, 2002a;Nevinsky and Buneva, 2002bCatalytic antibodies, 2005), were inactive in the presence of EDTA, while very small subfractions of human milk IgGs and sIgAs are Me 2þ -independent (Nevinsky et al, 2000b). We have recently shown that mammalian IgGs lose most bound metal ions during the standard procedure of purification to electrophoretic homogeneity (Polosukhina et al, 2006;Ikhmyangan et al, 2006). DNase pIgGs from the sera of MRL-lpr/lpr mice usually possess low activity after purification due to remaining intrinsically bound metal ions.…”
Section: Chromatography Of a Mixture Of Several Iggs On Dna Cellulosementioning
confidence: 94%